Reinventing the politics of knowledge production in migration studies: introduction to the special issue - Amelung, Nina; Scheel, Stephan; van Reekum, Rogier (Journal of ethnic and migration studies, 2024)
This special issue (SI) calls for reinventing the politics of knowledge production in migration studies. Academic migration research should make knowledge production an essential part of its research agenda if it wants to remain relevant in the transnational field of migration research. A risk of marginalisation stems from three interrelated tendencies: First, non-academic actors producing authoritative knowledge about migration have proliferated in recent years. Secondly, academic knowledge production is challenged both by counter-knowledge produced by social movements as well as new digital methods and information structures owned by policy-oriented and private actors. Thirdly, academics no longer hold a hegemonic position in the transnational field of migration research. The contributions to this SI interrogate the politics of knowledge production on migration along three lines of inquiry: (1) the enactment of migration as an intelligible object of government through practices of quantification, categorisation and visualisation; (2) the production of control knowledge in border encounters about subjects targeted as migrants and (3) the modes of thought seeking to unknow and re-know migration beyond dominant nation-state centric understandings. This introduction elaborates how the nine articles of the SI intervene in the politics of knowledge production in migration studies along these lines of inquiry.